2015
DOI: 10.1177/0731684415609139
|View full text |Cite
|
Sign up to set email alerts
|

Effects of seawater exposure on mode II fatigue delamination growth of a woven E-glass/bismaleimide composite

Abstract: The effects of seawater exposure on Mode II fatigue delamination growth of a woven E-glass Bismaleimide composite are investigated by end-notched flexure tests in this study. Dynamic mechanical analysis shows a strong plasticization effect of seawater immersion on the matrix material. Static tests of specimens after 2500 h of immersion in 50 C seawater reveal that the critical strain energy release rate (G IIC Þ is increased by 15.4%. This is mainly due to seawater effects of plasticization of the matrix, exte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…The difference of fracture mechanisms between dry and aged specimens were also observed in previous studies [160,168]. However, it has also been shown that the improvement could be only temporary and reversible as the damaging effect prevails in the longer term [162,204,205]. Moreover, the dry specimens had stable delamination resistance curves, while wet specimens under both conditions had increasing resistance with delamination growth.…”
Section: Mode I Delamination Behaviorsupporting
confidence: 72%
See 1 more Smart Citation
“…The difference of fracture mechanisms between dry and aged specimens were also observed in previous studies [160,168]. However, it has also been shown that the improvement could be only temporary and reversible as the damaging effect prevails in the longer term [162,204,205]. Moreover, the dry specimens had stable delamination resistance curves, while wet specimens under both conditions had increasing resistance with delamination growth.…”
Section: Mode I Delamination Behaviorsupporting
confidence: 72%
“…Moreover, the crack jump mechanism in woven composite makes the matter even worse. To overcome these disadvantages, an experimental compliance calibration (CC) approach is adopted in this study [173], which computes the effective crack length by Eq.…”
Section: Image-processing Algorithmmentioning
confidence: 99%
“…The primary advantage of BMI-based systems is the increase in service temperature range over conventional epoxies system from approximately 300 F-350 F to 400 F-450 F. 25 However, these composites can experience extremely severe environments involving high temperature, high humidity, and even sea fog exposure 26 during the service lifetime. Previous studies 27,28 reported that the glass transition temperature (T g ) of BMI matrix dropped significantly due to the plasticization effects of absorbed water. The hygrothermal-induced fiber-matrix interface failure in carbon/BMI composites was also observed by other researchers.…”
Section: Introductionmentioning
confidence: 99%
“…One of the most crucial engineering issues regarding the application of micro and nanoscale electronic devices in liquid environments is the need of being protected from the external harsh surroundings. This is mainly due to the risk of short-circuit caused by the absorption and permeation of water, which is generally also responsible of degradation of devices made of layered functional structures [1,2,3]. In this respect, delamination is one of the major modes of failure of organic and inorganic layered systems and consists of the weakening or loss of adherence between the different layers, resulting from mechanical strain mismatches or electrochemical reactions at the interfaces [4].…”
Section: Introductionmentioning
confidence: 99%